الكفايات: قراءة في الماهية وشروط الصياغة - بلخيري, سليمة (University of Eloued جامعة الوادي, 2018)
تسعى المنظومة التربوية الجزائرية في ظل التغيرات والتحولات المختلف الراهنة جاهدة إلى مواكبة التطور العلمي الرهيب الذي يشهده العالم المعاصر، وما يفرضه من استثمار في الرأس المال الفكري، إلى تبني مقاربات تضمن لها حضورا وسط هذا التنافس، وتعد مقاربة التدريس بالكفايات واحدة من المخططات التربوية التي عقدت عليها آمالا كبيرة لتفعيل دور التعليم نظرا للتراجع الكبير والملموس في الجانب النوعي منه، نهيك عن إلزامية التحيين والتجديد في الفعل البيداغوجي ونقله من سلطة المعلم إلى فاعلية التلميذ، فتتجاوز بذلك مناهج يتخللها ركام معرفي، إلى مناهج تستنطق الكفاءة عند المتعلم. من هنا يأتي هذا المقال محللا لمفهوم الكفاية، ومركزا على شروط صياغة منصوصها. Abstract : The Algerian educational system seeks to cope with the terrible scientific development witnessed by the modern world and the investment it requires in intellectual capital to adopt approaches that guarantee its presence in the midst of this competition. The approach of teaching competencies is one of the educational schemes held It has great hopes for activating the role of education due to the significant and tangible decline in the qualitative aspect. We ask that the modernization and renewal of the pedagogic act be carried out and transferred from the authority of the teacher to the effectiveness of the student. We move on to curricula that are permeated by knowledge. Of the learner. Hence, this article analyzes the concept of sufficiency, and focuses on the terms of the wording of its provisions.
Competencies: Reading the essence and drafting conditions.
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 04 جامعة الوادي
Keywords: الكفاية، منصوص الكفاية، مقارب التدريس بالكفايات; adequacy, provision of adequacy, approximation teaching competencies